The roles and contributions of the Hadhrami Arabs in Malaya, 1819 – 1969 / Latifah Abdul Latiff - Latifah, Abdul Latiff (2016)

(untitled)
This study examines the significant roles played by the Hadhrami Arabs and their contributions in the aspects of religion, education, publication, economics, politics, and administration of Malaya from 1819 until 1969. This study employs a qualitative research method. Library research is used in collecting data from published and unpublished documents, as well as records from the local archives and abroad, such as The National Archives of London, British Library, London, The National Archives of Singapore, National Library Board, Singapore, The National Archives Malaysia and its branches, The University of Malaya Library, and The National University Malaysia Library. All data are examined and analysed descriptively, analytically, and critically throughout the study. This study explores how the Hadhrami Arabs, a minority group of immigrants from Hadhramaut, Yemen, managed to prosper and hold important positions in the administration, politics, and economy of the Malay states. Furthermore, this research looks into the period of the founding of Singapore as a trading post by Stamford Raffles in 1819 whereby he managed to attract Arab traders to trade and to settle in Singapore. Moreover, the year 1969 marked the end of this study when South Yemen became independent with communist regime in power that practised the closed door policy regarding the migration of the Hadhrami Arabs and forbade those in the diaspora from returning home. Apart from their active involvement in the economy, administration, and politics of the Malay states, the Hadhrami Arabs also contributed immensely in the field of religious education, whereby several madrasahs or Arab schools were built to cater the needs of Muslim children. Waqf or endowment funds were also established from which income was collected to pay for the maintenance of madrasah, as well as for the teachers’ salary. In addition, they also built mosques and financed orphanages through the waqf fund, as well as donating lands for graveyards. However, the involvement of Hadhrami iv Arabs in the aspects of administration and politics of the Malay states had been looked upon with suspicion by the British. Thus, this study examines how the British responded towards the roles played by the Hadhrami Arabs and their involvement in the administration of religion, madrasah education, publication, politics, administration, and economics in Malaya. It also chronicles the Hadhrami Arab-British relationship in the 19th and the 20th century in Malaya. Apart from that, this study analyses factors that led to the decline of the Hadhrami Arab descents in Malaya after the Second World War, particularly in politics and economy that eventually led to the shrinking of Hadhrami Arabs’ dominance in the economy, as well as the identity crisis faced by the younger generation of the Peranakan Arab. Nevertheless, based on the information gathered, this study could be used to support and to strengthen the theory of the Arab factor in the social, economic, and political development in Malaya, by highlighting the contributions made by the Hadhrami Arabs; especially the Sayyids in the 19th and the 20th centuries, as they also contributed to the historical development of Malaysia.